Pure Intrinsic brain stem epidermoid cyst: Case report, review of the literature and new classification - Teegala, Ramesh (Nepal Journal of Neuroscience, 2017)
Epidermoid cysts are one of the uncommon slow growing lesions. There is some amount of controversy prevailing in the uniform understanding of these among the researchers regarding the nomenclature of these lesions. With a critical review of reported cases, author demarcated four different anatomical types of brain stem epidermoids and proposed a new classification system for a better understanding of the natural history. Four years female child presented with insidious onset left sixth and seventh cranial nerve palsy with right hemiparesis. Radiological evaluation revealed a pure intrinsic brain stem cystic lesion. Surgical decompression of the cyst was done, and the child recovered well. Histopathological examination was an epidermoid cyst. Brain stem epidermoids are uncommon, and there is no age or sex predilection. Based on the epicenter these tumors could be classified into four different types. Adequate surgical excision is the hallmark in the treatment. Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, page: 33-41